Trabalho e o adoecimento mental: uma análise no setor de transporte coletivo urbano da região metropolitana de Belo Horizonte - Julia Nogueira Dorigo (2009)
The objective of this study was to understand the high taxes of work absenteeism in the population of bus drivers from a company situated at the Metropolitan Region of Belo Horizonte. The companys administration manager brought up this complaint to a psychologists group from UFMG. The work began with an epidemiological study that confirmed the bus drivers as the focus of this study. They represented 66% of all thecompany employees that werent working at that moment and their main symptoms were depression (20%) and anxiety (13%). Next, were realized the stages of Ergonomic Work Analysis (EWA) and Psicosociological Work Analysis (PWA), that tried to comprehend the activity that those workers did, as well as their subjective impacts. Two study cases were also realized, as part of the PWA, which allowed a better comprehension of the problems identified at the EWA stage, at the individuals perspective. On the first study case, we present a bus driver that has Posttraumatic Stress Disorder (PSTD) (F 43.1, CID-10) acquired at the work. In the second study case, we present a bus driver that was able to preserve his heath, at some level, besides being exposed to an unhealthy work organization. This work pointed that the reasonwhy this bus drivers got sick is associated to theirs unhealthy work organization, imposed to them by their company, and not exclusively linked to individual factors, such as were suggested, in the beginning, by the companys administration staff.